The Global Sustainability Reporting Landscape and the Role of Public Accountants in Providing Assurance: Enhancing the Credibility and Integrity of Sustainability Reports, and Creating Corporate Value - Alfara, Dicky Maiza; Nugrahanti, Trinandari Prasetya (Eastasouth Institute, 2025)
The global dialogue on a sustainable economy has gained momentum due to a growing recognition among various stakeholders—such as investors, consumers, and policymakers—of the importance of integrating environmental, social, and governance (ESG) factors into economic and business practices. This growing awareness, along with commitments from world leaders, has made it essential for companies across various industries and governments to report their sustainability efforts through sustainability reporting to enhance their value in the eyes of stakeholders and investors.This study aims to describe and analyze the global development of sustainability reporting and examine the role of public accountants or external auditors in providing assurance services that enhance the credibility and integrity of these reports. The research employs a descriptive analysis literature review, gathering published global survey reports and previous studies from 2020 to 2024 in international journals and selecting them based on relevance, scope, and data quality.The findings indicate a significant global increase in sustainability reporting, reflecting companies' growing recognition of its importance not only for supporting environmental conservation but also for creating value for stakeholders and investors. Additionally, analyses from surveys and prior research demonstrate that the inclusion of assurance services in sustainability reports is positively correlated with the market value of company shares, thereby enhancing corporate value. Assurances provided by public accountants or external auditors further contribute to the credibility and integrity of sustainability reports, ultimately strengthening trust among stakeholders.